2017
DOI: 10.1007/s11368-017-1797-y
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in the content of dissolved organic matter in arable soils

Abstract: Purpose The aim of this paper has been to determine the seasonal changes in the content of dissolved organic matter (DOM) in the soils under agricultural use based on assaying changes in dissolved organic carbon (DOC) and dissolved nitrogen (DNt) as well as determining the factors which can define the DOM in soils. Materials and methods The research has involved the soils under agricultural use sampled in the Kujawsko-Pomorskie province (Poland). Phaeozems and Luvisols were sampled from the depth of 0-30, 30-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…Nitrogen enrichment decreases soil DOC concentration due to the chemical stabilization of organic carbon [56] and the stimulation of the microbial mineralization rate, which increases DOC consumption [57]. Results of the current study, however, revealed that nitrogen enrichment stimulated soil DOC concentration, which is consistent with Shi et al [58] and Wei et al [52]; this could be attributed to the nutrient status of the soil [59,60]. Rosa et al [60] pointed out that soil DOC significantly correlated with SOC and total N. Soil DOC increased with an increasing N rate (Figure 4b), probably due to aboveground plant biomass, which was returned to the soil annually.…”
Section: Effects Of Chronic Nitrogen Enrichment On Soil Biochemical Propertiessupporting
confidence: 87%
“…Nitrogen enrichment decreases soil DOC concentration due to the chemical stabilization of organic carbon [56] and the stimulation of the microbial mineralization rate, which increases DOC consumption [57]. Results of the current study, however, revealed that nitrogen enrichment stimulated soil DOC concentration, which is consistent with Shi et al [58] and Wei et al [52]; this could be attributed to the nutrient status of the soil [59,60]. Rosa et al [60] pointed out that soil DOC significantly correlated with SOC and total N. Soil DOC increased with an increasing N rate (Figure 4b), probably due to aboveground plant biomass, which was returned to the soil annually.…”
Section: Effects Of Chronic Nitrogen Enrichment On Soil Biochemical Propertiessupporting
confidence: 87%
“…The regression model analysis of the dependences of the soil SOC development in the field conditions clarifies the basic soil properties as the most important factor. The available humus content models refer mainly to the SOC and soil total nitrogen (STN) assessments [86][87][88], and the time of sampling [89]. Malkina-Pykh [90] investigated the behaviour of humus in the Sod-Podzolic soils.…”
Section: Discussionmentioning
confidence: 99%
“…Moreno et al [54] found that long-term conservation tillage increased TOC content and the quality and stability of SOM. The labile fractions of organic carbon are more sensitive to changes in soil management practices [55]. Both tillage treatments and the application of cattle manure as well as the addition of legumes in crop rotation have increased SOC, enzymatic activity and improved soil fertility on the OF.…”
Section: Discussionmentioning
confidence: 99%